Five-level cascaded H-bridge inverter for renewable energy applications - Md. Hazrat Ali; Emtiaz Ahmed Mainul; Tawfikur Rahman; Md. Shabuj Hossen; Md. Kamrul Alam Khan; Mohammad Obaidur Rahmann (Institute of Advanced Engineering and Science, 2023)
This paper presents a five-level inverter based on the phase-disposition pulse width modulation (PD-PWM) technique for renewable energy applications. The conventional cascaded H-bridge (CHB) five-level inverter structure is reproduced, and an LC filter is designed to get optimum results from the inverter output. Two batteries are used as renewable energy sources to investigate the performance of the designed inverter. The system can provide 220 volts and 50 Hz AC supply with a 6.9 kW power supply to the load/grid. The designed output is compared with filter and without filter circuit. It provides sinusoidal voltage and current output with a very low total harmonic distortion (THD) of 2.75% which is compliant with IEEE 519 standards. MATLAB/Simulink software tool is used for the entire design. The inverter’s output is graphically represented, and discussed various parameters like switching frequency, THD, modulation index, and rated voltage.